A Cautionary Tale from Testosterone An Unauthorized Biography - Martin, Craig (Bulletin for the Study of Religion, 2021)
Craig Martin reviews Testosterone: An Unauthorized Biography (Harvard University Press 2019) by Rebecca M. Jordan-Young and Katrina Karkazis. Testosterone examines the history and uses of the hormone in biomedical research. Conventionally understood as the male sex hormone, Martin learns that the construction of this idea is far more complicated and marred by politics of classification and definition. Martin suggests that Jordan-Young and Karkazis’ study models the kind of questions schoalrs of religion would do well to ask about their own data.